Pengembangan Video Pembelajaran OpenStreetMaap untuk Pembuatan Peta Digital Format Shapefile Menggunakan Geofabrik - Hanif Muhasan; Sunar Rochmadi (Jurnal Pendidikan Teknik Sipil, 2022)
ABSTRACTThe objectives of this study is developing videos based learning of OpenStreetMap for producing digital maps within shapefile format using Geofabrik at Geomatics Practice II courses. This research is using method of research and development or research and development (R&D) with a 4D model based Thiagarajan. The technique of collecting data is through questionnaires. While data analysis were carried out using quantitative descriptive data analysis techniques.The results of this study were reviewed at each stage of the development of the 4D model are: (1) The define stage produces is the need of explanation about OpenStreetMap for producing digital maps in shapefile format using Geofabrik. The need becomes the substance of video based learning product which is developed. (2) The design stage produces the concept of developed media, suitability of materi, storyboard and narrative material, layout of media based learning, systematics of video and layout of images in the video, learning scenarios, and media is produced in the form of  video based learning with techniques screen capturing within format *.mp4 which duration 17 minutes 11 seconds and the file size is 497 MB. (3) The development phase produces an assessment of the feasibility of the developed media based learning product. Based on the assessment of material experts the results obtained were 96.97% in the very feasible category, from the media experts the results obtained were 87.81% with the very feasible category and based on the user's assessment the results obtained were 88.51% in the very feasible category. (4) Disseminate stage is done by disseminating video based learning products through YouTube channel of  video based learning creator and the submission of  video based learning products to lecturers of Geomatics Practicum II courses in the Department of Education Civil Engineering and Planning Faculty of Engineering Yogyakarta State University.ABSTRAKTujuan dari kajian ini adalah mengembangkan video pembelajaran OpenStreetMap untuk pembuatan peta digital format shapefile menggunakan Geofabrik pada mata ajar Geomatika II. Kajian ini merupakan kajian dan pengembangan atau research and development (R&D) yang mengacu pada model 4D (four-D) oleh Thiagarajan. Teknik pengumpulan data dilakukan dengan angket. Sedangkan analisis data dilakukan dengan teknik deskriptif kuantitatif. Hasil dari kajian ini ditinjau pada masing-masing tahapan pengembangan model 4D antara lain: (1) Tahap define menghasilkan kebutuhan penjelasan OpenStreetMap untuk pembuatan peta digital format shapefile menggunakan Geofabrik. Kebutuhan tersebut menjadi substansi dalam produk video pembelajaran yang dikembangkan. (2) Tahap design menghasilkan konsep media yang dikembangkan, materi yang sesuai, storyboard dan narasi materi, layout media pembelajaran, penyusunan video secara sistematis dan tata letak gambar yang disisipkan dalam video, skenario pembelajaran, serta media yang dihasilkan berupa video pembelajaran dengan teknik screen capturing berformat *.mp4 yang berdurasi 17 menit 11 detik dan ukuran file sebesar 497 MB. (3) Tahap development menghasilkan penilaian tingkat kelayakan produk media pembelajaran yang dikembangkan. Berdasarkan penilaian ahli materi diperoleh hasil sebesar 96,97% dengan kategori sangat layak, dari ahli media diperoleh hasil sebesar 87,81% dengan kategori sangat layak serta berdasarkan penilaian pengguna diperoleh hasil 88,51% dengan kategori sangat layak. (4) Tahap disseminate dilakukan dengan penyebarluasan produk video pembelajaran melalui kanal YouTube.